Environmental and Social Safeguards Training in Ethiopia - Ambaw, Gebermedihin; Belay, Berhanu; Ngungu, Elizabeth; Kwaw, Adams (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate change poses significant challenges and risks to agriculture, particularly affecting smallholder farmers who are integral to Ethiopia's food systems. These farmers face increased pressures from shifting weather patterns, water scarcity, and other climate-related stresses that jeopardize their livelihoods and productivity. Adopting Climate-Smart Agriculture (CSA) and Climate Information Services (CIS) to address these issues and build resilience is crucial. CSA encompasses practices and technologies that boost agricultural productivity while reducing greenhouse gas emissions and adapting to climate change. CIS offers farmers timely and relevant climate information, enabling informed decision-making. In Ethiopia, the Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project is leading efforts to promote CSA and CIS. The AICCRA Ethiopia cluster integrates environmental and social (E&S) safeguards into climate-related initiatives through partnership and collaboration with various stakeholders. These safeguards aim to protect ecosystems and communities from the potential negative impacts of CSA interventions. This report highlights the E&S safeguards training conducted on August 30 and 31, 2024, for 16 participants, three of whom were women. The training engaged partners from Melkassa, Kulumsa, Debrezeit Agricultural Research Centers, Inter Aide, the Ministry of Agriculture, universities, and the private sector (Lersha). It strengthened stakeholders' capacity to incorporate E&S safeguards into their climate-related projects. The report outlines the process of identifying potential environmental and social risks associated with climate-smart projects and proposing strategies to mitigate these risks. By addressing these concerns, the training supports the advancement of agricultural resilience while upholding principles of equity and sustainability.